Characterization of polycrystalline lead oxide for application in direct conversion X-ray detectors - O. Semeniuk (Nature Portfolio, 2017)
Abstract While polycrystalline lead oxide (poly-PbO) is known to be one of the most promising photoconductors for utilization in X-ray detectors, its major performance parameters such as charge yield and mobility-lifetime product (μτ) are still not well established and require further investigation. Combining the conventional X-ray induced photocurrent and pulse height spectroscopy techniques we examine the X-ray photogeneration and recombination processes in poly-PbO. The measurements indicate that the amount of energy required to release a single electron hole pair W ± (inverse of charge yield) strongly depends on applied electric field and at 10 V/μm reaches ~20 eV/ehp. Fitting the measured pulse height spectra with the Hecht formula provided μτ for holes and electrons to be 4.1 × 10−8 cm2/V and 10−9 cm2/V, respectively. Obtained μτ values combined with recently reported mobility values of charge carriers in PbO suggest a new direction towards improvement of PbO technology by incorporation of Frisch grid or X-ray transistor architectures.